2015
DOI: 10.1186/s12891-015-0685-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between work-related biomechanical risk factors and the occurrence of carpal tunnel syndrome: an overview of systematic reviews and a meta-analysis of current research

Abstract: BackgroundOccupational risks for carpal tunnel syndrome (CTS) have been examined in various occupations, and several systematic reviews (SRs) have been published on this topic. There has been no critical appraisal or synthesis of the evidence in the SRs. The aims of this study are (1) to synthesise the observational evidence and evaluate the methodological quality of SRs that assess the effect of biomechanical risk factors on the development of CTS in workers, (2) to provide an update of current primary resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 66 publications
4
105
0
8
Order By: Relevance
“…A recent overview of systematic reviews and a metaanalysis of current research concluded that there is high evidence for an increased risk of CTS in activities requiring a high degree of repetition and forceful exertion while the evidence for vibration and non-neutral wrist postures appears moderate and low respectively (33).…”
Section: Discussionmentioning
confidence: 99%
“…A recent overview of systematic reviews and a metaanalysis of current research concluded that there is high evidence for an increased risk of CTS in activities requiring a high degree of repetition and forceful exertion while the evidence for vibration and non-neutral wrist postures appears moderate and low respectively (33).…”
Section: Discussionmentioning
confidence: 99%
“…[12] Magnetic resonance imaging has revolutionized the assessment of entrapment neuropathies. [13] Sangwan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Además, pueden optar a un tratamiento médico temprano disminuyendo el compromiso de la patología en algunos casos. Por otro lado, los pacientes que acuden a CAS, en general, no realizan actividades laborales que requieran de trabajo manual extremo o muy repetitivo, minimizando a este grupo de la población con mayor riesgo de desarrollar STC 34 . Destaca el bajo número de pacientes excluidos por cirugía previa de STC, esto pudiese ser explicado por las características de la población estudiada, o bien por falta de información en el diagnóstico de derivación.…”
Section: Discussionunclassified